2023
DOI: 10.1186/s10020-023-00614-9
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-propionic acid alleviates chondrocytes inflammation and osteoarthritis via the AhR/NF-κB axis

Abstract: Background Osteoarthritis (OA) is a common chronic disease characterized by chronic inflammation and extracellular matrix degradation. Indole-3-propionic acid (IPA) is a tryptophan metabolite secreted by intestinal flora, which can exert anti-inflammatory effects in a variety of diseases. In this study, we further investigated the potential therapeutic role of IPA in OA and the underlying mechanism. Methods IL-1β was utilized to induce chondrocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…In regard to the downregulation of cardiac NNMT by IPA, it has been reported that the proinflammatory cytokines, such as IL-6 and TNF-a, elicit significant induction of NNMT expression. 37 Since IPA has whole-body anti-inflammatory effects in multiple disease models, 23,29,38,39 we examined whether IPA could downregulate cardiac NNMT through an anti-inflammatory response. The expression of proinflammatory cytokine TNF-α is increased in the mice heart upon HFpEF diet feeding and IPA supplementation decreased TNF-α expression, in accordance with the expression of NNMT (Figure 4I and 4J).…”
Section: Resultsmentioning
confidence: 99%
“…In regard to the downregulation of cardiac NNMT by IPA, it has been reported that the proinflammatory cytokines, such as IL-6 and TNF-a, elicit significant induction of NNMT expression. 37 Since IPA has whole-body anti-inflammatory effects in multiple disease models, 23,29,38,39 we examined whether IPA could downregulate cardiac NNMT through an anti-inflammatory response. The expression of proinflammatory cytokine TNF-α is increased in the mice heart upon HFpEF diet feeding and IPA supplementation decreased TNF-α expression, in accordance with the expression of NNMT (Figure 4I and 4J).…”
Section: Resultsmentioning
confidence: 99%
“…Given the documented ability of IL-1β to induce ADAMTS5 up-regulation in human chondrocytes, , we determined the expression level of IL-1β in Tp-treated hCMEC/D3 cells. After stimulation with Tp at an MOI of 50:1 for 24 h, the expression of IL-1β was detected by RT-qPCR and ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that IL-1β had been demonstrated to induce the up-regulation of ADAMTS5 in human chondrocytes, , we also investigated whether Tp regulated the expression of ADAMTS5 through IL-1β. Our findings revealed that Tp induced the production of IL-1β in hCMEC/D3 cells and that recombinant human IL-1β promoted the expression of ADAMTS5 in these cells, which was consistent with previous studies. , Moreover, the inhibition of IL-1β using diacerein significantly reduced the production of ADAMTS5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations